2013
DOI: 10.3171/2013.8.peds13212
|View full text |Cite
|
Sign up to set email alerts
|

Etiology associated with developing posthemispherectomy hydrocephalus after resection-disconnection procedures

Abstract: Object The authors sought to determine if clinical epilepsy variables, maximum daily temperature (Tmax), and blood and CSF findings were associated with the risk of developing hydrocephalus after first-time resection-disconnection hemispherectomy. Methods Patients who underwent cerebral hemispherectomy in whom a standardized perioperative protocol was used, including the use of ventriculostomies (n = 79)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…5,[25][26][27] Meningitis developed in 10% of patients during their hospitalization, which was noted to be the second most common complication in our series, again consistent with the literature. 8,15,28,29 Given the lack of an ICD-9-CM code for aseptic meningitis, we could not ascertain the exact contribution of this common and expected complication to our observed overall rate of meningitis of 10%. In fact, patients often receive prolonged courses of prophylactic steroids postoperatively as a method to treat aseptic meningitis, which is believed to be caused by the large amount of tissue breakdown products and debris within the resection cavity irritating the meningeal layers of the brain after surgery.…”
Section: Resultsmentioning
confidence: 95%
“…5,[25][26][27] Meningitis developed in 10% of patients during their hospitalization, which was noted to be the second most common complication in our series, again consistent with the literature. 8,15,28,29 Given the lack of an ICD-9-CM code for aseptic meningitis, we could not ascertain the exact contribution of this common and expected complication to our observed overall rate of meningitis of 10%. In fact, patients often receive prolonged courses of prophylactic steroids postoperatively as a method to treat aseptic meningitis, which is believed to be caused by the large amount of tissue breakdown products and debris within the resection cavity irritating the meningeal layers of the brain after surgery.…”
Section: Resultsmentioning
confidence: 95%
“…These findings complement those of prior studies by our group showing a limited association of CNS and non-CNS infections with fevers and altered blood and CSF values in all types of pediatric epilepsy surgery cases, as well as an association between etiology and posthemispherectomy hydrocephalus requiring CSF shunts. 11,12 Taken together, these findings indicate that multiple clinical variables are associated with the development of fever and altered blood and CSF laboratory studies after cerebral hemispherectomy involving resection-disconnection procedures, including the underlying seizure etiology and age at surgery. For the practicing neurosurgeon, the best predictor of CNS Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In the case of functional hemispherectomy, aetiology seems to be the decisive factor than the inflammation induced by the surgery. One study found higher rates of hydrocephalus and shunting procedures in association with hemimegalencephaly and central nervous system infection and less in association with cortical dysplasia and Rasmussen’s encephalitis 10. This was explained by the varying CSF flow dynamics in association with the different aetiologies.…”
Section: Discussionmentioning
confidence: 99%